Expected Time to Recruitment in Man Power Planning Using EE-Distribution - , M.Chitra, S. Parthasarathy (International Journal of Scientific Research and Management (IJSRM), 2016)
In any organization, successive exit of personnel leads of wastage in the form of man hours.The breakdown of the organization is triggered whenever the cumulative loss of manpower exceeds aparticular level called threshold, beyond which the organization cannot sustain due to loss of protectivelyGupta and Kundu [2001] developed an Exponentiated Exponential (EE) distribution with two parametersnamely scale and shape parameter. The current work is focused on shape parameter of EE distribution. Tocompute the expected time to reach the recruitment and its variance is found. The analytical results arenumerically illustrated by assuming specific distributions.